Cardiff sciSCREEN: A model for using film screenings to engage publics in university research. (1st January 2017) - Lewis, Jamie; Bisson, Susan; Swaden Lewis, Katie; Reyes-Galindo, Luis; Baldwin, Amy
Abstract : Cardiff sciSCREEN is a public engagement programme that brings together local experts and publics to discuss issues raised by contemporary cinema. Since 2010, Cardiff sciSCREEN (short for science on screen) has exhibited more than 50 films alongside short talks and discussions that draw on a range of disciplinary perspectives to explore the broad repertoire of themes found within different film genres. The aim of Cardiff sciSCREEN is to increase the local community's access to university research, while enabling university staff and students to engage a variety of publics with their work. In this paper, we first describe our method of public engagement, and then draw on data from a research survey we administered to sciSCREENers to discuss the relationship between the theory and practice of public engagement. Using research from public understanding of science (PUS), public engagement with science and technology (PEST), science and technology studies (STS) and film literacy, we discuss the ways in which our flexible characterization of science has made the programme inclusive, attracting a wide and varied audience. We consider the benefits of cross-disciplinary perspectives when communicating and engaging contemporary developments in science, where the term 'science' is taken to stand for the breadth of academic research and not merely the natural sciences, as well as discussing the importance of space in public engagement events.